Depression, anxiety and stress among HIV patients in East Coast Malaysia - Abdul Hadi, Azwanis; Mohd Mustapha, Nur Syuhada; Ahmad Hafidzi, Nur Farhana; Shaari, Nur Sahira; Pasi, Hafizah; Osman, Iskandar Firzada; Che Yusof, Mohd Daud (Quality Scientific Publishing, 2019)
Introduction: HIV infection is a chronic disease with multiple challenges that could affect the psychological well-being of patients. Objective: The objective of this research was to determine the prevalence of depression, anxiety and stress among HIV patients and its significant associated factors. Methodology: This is a cross-sectional study which was carried out in two health centers in a town in the East Coast of peninsular Malaysia. A total of 42 patients with HIV were recruited via convenience sampling. Those who fulfilled the inclusion and exclusion criteria completed a validated set of Malay version of DASS-21 questionnaire. Data was analyzed using IBM SPSS Statistics. Result: The prevalence of depression,anxiety and stress among a adult HIV patients in communitity follow-up were 33.3%, 28.6% and 21.4% respectively. Marital status was significant associated with both depression and stress. While CD4 count was found to be significantly associated with anxiety